Historiador de processos como um microsserviço: uma abordagem para a Indústria 4.0 - Domingues, Felipe de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Understanding the behavior of industrial processes to generate efficiency in the production line and provide inputs for decision-making in the management of an organization is fundamental. The process historian is a system designed to collect and store time series process data that allows the transformation of raw data into process intelligence. The need for a system to store historical data and make it available for other applications is an important feature in the scenario of constant digital transformation, therefore, the creation of a repository that allows the development of intelligence for later availability of this information through a human-machine interface is indispensable. The present work aims to develop a service for real-time monitoring and historical availability of the process variables of an industrial pilot plant. The state of the art was studied within the industrial context. The biggest challenge found was to integrate different technologies that encompass the development of the application within an embedded platform. The pilot plant has its architecture based on microservices that basically transform analog data into digital data, which are made available via framework through an application programming interface. The solution is to integrate this architecture with an application that consists in consuming this data through a specific communication protocol and storing it in a local database, feeding the process historian. The result is a service that is automatically activated when the plant is turned on, with an intuitive, low complexity and timely interface, accessible through the network, and that can be displayed with the touch screen attached to the plant or a mobile device, having dynamic, responsive and navigable graphics display, with history query functionality.

Entender o comportamento dos processos industriais para gerar eficiência na linha de produção e o fornecimento de insumos para tomadas de decisão na gestão de uma organização é fundamental. O historiador de processos é um sistema projetado para coletar e armazenar dados de processos de série temporal que permite transformar dados brutos em inteligência de processo. A necessidade de um sistema de armazenamento de dados históricos e sua disponibilização para outras aplicações é uma característica importante no cenário de constante transformação digital, portanto, a criação de um repositório que permita o desenvolvimento de inteligência para posterior disponibilização dessas informações através de uma interface homem-máquina é indispensável. O presente trabalho objetiva o desenvolvimento de um serviço de monitoramento em tempo real e disponibilização de histórico das variáveis de processos de uma planta piloto industrial. Foi realizado o estudo do estado da arte dentro do contexto industrial. O maior desafio encontrado foi integrar diferentes tecnologias que englobam o desenvolvimento de aplicação dentro de uma plataforma embarcada. A planta piloto possui a sua arquitetura baseada em microsserviços que basicamente transformam dados analógicos em digitais, os quais são disponibilizados via framework através de uma interface de programação de aplicações. A solução é integrar essa arquitetura a uma aplicação que consiste em consumir esses dados através de um protocolo de comunicação específico e armazená-los em um banco de dados local, alimentando o historiador de processos. O resultado é um serviço automaticamente ativado ao ligar a planta, com uma interface intuitiva, de baixa complexidade e tempestivo, acessível através da rede, podendo ser exibido com o monitor touch acoplado na planta ou um dispositivo móvel, tendo exibição de gráficos dinâmicos, responsivos e navegáveis, com funcionalidade de consulta de histórico.
Process historian as a microservice: an approach for Industry 4.0
Keywords: Database; Data warehousing; Banco de Dados; Internet das Coisas para Indústria; Armazenamento de dados; Internet